Implementation of Rational Emotive Behavior Therapy in Overcoming Deviant Sexual Orientation: A Case Study - Safitri, Bella; Noviza, Neni; Dewi, Emi Puspita (Grief and Trauma, 2024)
Deviant sexual orientation, particularly same-sex attraction, is a complex issue that often results from various internal and external factors. This research formulates several key issues: what is the form of deviant sexual orientation in the subject, what factors cause this deviant sexual orientation, and how can Rational Emotive Behavior Therapy (REBT) be applied to address it? This study uses a qualitative approach with a case study method, focusing on a subject, referred to as "client 'R'," who is an inmate at the Class II A Palembang Women's Prison. Data collection techniques include observation, interviews, and documentation, while data analysis involves pattern matching, explanation, and time series analysis. The findings indicate that client 'R' exhibits deviant sexual orientation, specifically a lesbian attraction to other women. The factors contributing to this behavior include environmental influences such as the absence of men in the prison and the lack of private spaces for inmates to fulfill their sexual needs with lawful partners. After five counseling sessions using REBT, client 'R' began to recognize that her behavior was against her natural inclinations as a Muslim and that it was strongly opposed by religious beliefs. Additionally, she became aware of the negative consequences, including the potential alienation from her family and exposure to health risks like HIV/AIDS. As a result, client 'R' showed a willingness to change her irrational (lesbian) mindset into a more rational one, guided by her values and understanding of the consequences.